Context-aware mobile applications development framework - Gwaro, Ronald (Strathmore University, 2013)
Mobile application development follows a number of strategies and approaches. Recent developments in mobile applications tend to consider context to be key. This has necessitated the need for context-aware mobile applications. To fully understand mobile applications and their components, this research separates core application logic from adaptive functionality and then applies qualitative and quantitative research techniques to investigate and come up with a framework for the development of context-aware mobile applications. The research identifies the factors affecting mobile application development as; Mobile device characteristics; Mobile application development platform; Changes in the mobile environment; Mobile application operating platform; Cellular network capabilities; Human and mobile device interaction; Application consistency across different mobile devices and platforms; Nature of content and service delivery; Mobile application performance and Mobile application security considerations. The technologies used in mobile application development are identified and broadly classified as communication technologies, development platforms technologies, middleware technologies, presentation technologies and security technologies. The research findings were used to build a framework for mobile applications development using context-awareness analogy. The framework consists of two main categories of core application logic and the adaptive functionality. The core application logic has six components and each contain the most critical feature the developer should emphasize on. The adaptive functionality also has five components that the mobile application developer should consider and each contains the most critical features for emphasis. The framework is then covered on each side by the mobile application security considerations. Mobile application security affects many of the components in the framework and therefore must be considered at the component level.
Research thesis submitted in partial fulfillment for the degree of Master of Science in Information Technology
Keywords: device characteristics; development platform; mobile environment; operating platform; cellular network capabilities; application consistency; service delivery; application performance and mobile security